International experiences in the development and implementation of guideline-based quality indicators: a qualitative study. Issue 1 (19th January 2021) - Nothacker, Monika; Bolster, Marie; Steudtner, Mirco; Arnold, Katrin; Deckert, Stefanie; Becker, Monika; Kopp, Ina; Schmitt, Jochen
Abstract : Objectives: Evidence-based clinical guidelines play an important role in healthcare and can be a valuable source for quality indicators (QIs). However, the link between guidelines and QI is often neglected and methodological standards for the development of guideline-based QI are still lacking. The aim of this qualitative study was to get insights into experiences of international authors with developing and implementing guideline-based QI. Setting: We conducted semistructured interviews via phone or skype (September 2017–February 2018) with guideline authors developing guideline-based QI. Participants: 15 interview participants from eight organisations in six European and North American countries. Methods: Organisations were selected using purposive sampling with a maximum variation of healthcare settings. From each organisation a clinician and a methodologist were asked to participate. An interview guide was developed based on the QI development steps according to the 'Reporting standards for guideline-based performance measures' by the Guidelines International Network. Interviews were analysed using qualitative content analysis with deductive and inductive categories. Results: Interviewees deemed a programmatic approach, involvement of representative stakeholders with clinical and methodological knowledge and the connection to existing quality improvement strategies important factors for developing QI parallel to or after guideline development. Methodological training of the developing team and a shared understanding of the QI purpose were further seen conducive. Patient participation and direct patient relevance were inconsistently considered important, whereas a strong evidence base was seen essential. To assess measurement characteristics interviewees favoured piloting, but often missed implementation. Lack of measurability is still experienced a serious limitation, especially for qualitative aspects and individualised care. Conclusion: Our results suggest that developing guideline-based QI can succeed either parallel to or following the guideline process with careful planning and instruction. Strategic partnerships seem key for implementation. Patient participation and relevance, measurement of qualitative aspects and piloting are areas for further development. Trial registration number: German Clinical Trials Registry (DRKS00013006).